Keeping athletes healthy at the 2020 Tokyo Summer Games: Considerations and illness prevention strategies - Keaney, L. C.; Kilding, A. E.; Merien, F.; Dulson, D. K. (Frontiers in Physiology, 2019)
Keeping athletes healthy will be important for optimal athletic performance at the 2020 Tokyo Summer Olympic and Paralympic Games. Athletes will be exposed to several stressors during the preparatory and competition phases of the Summer Games that have the potential to depress immunity and increase illness risk. This mini-review provides an overview on effective and practical stressor-specific illness prevention strategies that can be implemented to maintain and protect the health of Olympic and Paralympic athletes.